2019
DOI: 10.1371/journal.pone.0214434
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in human balance performance from 6-18 years of age: A systematic review and meta-analysis

Abstract: Background The process of growing leads to inter-individual differences in the timing of growth, maturational, and developmental processes during childhood and adolescence, also affecting balance performance in youth. However, differences in balance performance by age and sex in youth have not been systematically investigated yet. Objective The objective of the present study was to characterize and quantify age- and sex-related differences in balance performance in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 80 publications
(95 reference statements)
11
38
0
5
Order By: Relevance
“…Differences between sexes are equivocal in the literature. Other researchers report no significant sex differences in balance skills at the age of 5–6 [16, 32, 34, 35]. It may be assumed that differences in the obtained results may depend on the use of different methods, measuring platforms or tests, different numbers of study participants or different age groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Differences between sexes are equivocal in the literature. Other researchers report no significant sex differences in balance skills at the age of 5–6 [16, 32, 34, 35]. It may be assumed that differences in the obtained results may depend on the use of different methods, measuring platforms or tests, different numbers of study participants or different age groups.…”
Section: Discussionmentioning
confidence: 97%
“…In turn, boys tend to spend more time engaged in moderate-to-vigorous physical activity and achieve better results in activities which require more speed and strength [21, 22, 23, 24]. Consequently, boys may be at an advantage over girls in terms of proactive balance as they can compensate worse balance with greater muscle strength [35]. It is possible that maturational slowness of the vestibular function seen in young boys is one of the factors responsible for the fact that boys are prone to be more active than girls [32, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Balance is important during activities of daily life as well as in sports and poor balance is associated with an increased risk of falling and sustaining injuries [1]. This is particularly important for children as balance performance does not reach the adult-level before late adolescence due to maturation processes of the postural control system [2]. According to Shumway-Cook and Woollacott [3], a distinction is made between static balance where the base of support and the ground remain stationary and only the center of mass moves (e.g., standing on a firm floor) and dynamic balance where the base of support and/or the ground move and the center of mass shifts (e.g., walking).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to balance performance in youth, findings on sex-related differences are rather inconclusive. For example, a systematic review with meta-analysis [2] examining age-and sex-related differences in balance performance in youth found inconsistent results. More precisely, girls showed superior static balance (standardized mean difference [SMD] = 0.33), while boys performed better in proactive conditions (SMD = − 0.15) and almost no difference was found concerning measures of dynamic balance (SMD = − 0.02).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, men are more likely to sway and cause physical instability than women because of their greater COP displacement during postural control [15]. Static and dynamic exercises show that women are excellent in maintaining static balance, affording posture stabilization and body balance maintenance [16]. Previous studies have shown that men have greater COP displacements after open-eyes/closed-eyes balance training, indicating that men are more unstable than women [17].…”
Section: Introductionmentioning
confidence: 99%